MEKANISME PENYELESAIAN TINDAK PIDANA KORUPSI OLEH LEMBAGA NEGARA KOMISI PEMBERANTASAN KORUPSI (KPK) - Prawira, Rosmala Dewi Sakti (PROGRESIF: Jurnal Hukum, 2016)
Treatment of the crime of corruption is not only the authority of the institution of the police and the Attorney General, because after the establishment of the Act Number 30 of 2002 years, that gave birth to a new institution which has the authority for the handling of corruption committed by state officials. The performance of the Commission's laudable once criticized, praise should be given for the period KPK now had been incised achievement. With the slogan Corruption kills the nation KPK summarize perfectly. Corruption is a destructive force that hit the core of the democratic Indonesia